Mosque as a multifunctional institution: an evaluation of users' perception on two community mosques in Malaysia / Muhammad Fakhar Muhammad Nur - Muhammad Nur, Muhammad Fakhar (2015)
A community mosque IS an important facility located within the Malaysian neighbourhood. It is a place for the Muslim community to gather for the purpose of worship and as a community development centre. The research attempts to gain an understanding on the multiplicity of function of a community mosque through users feedback on visitation, usage trend, and their evaluation on the spatial conditions of the community mosque. The research employed a mixed methodology approach which combines qualitative and quantitative methods to examine two case study community mosques. The scope of the primary data was limited to two community mosque representations which arc Al-Hasanah Mosque in Bandar Baru Bangi and As-Salam Mosque in Puchong as case study. Instruments of research were architectural elements inventory, walk through survey, interview and questionnaires. The research revealed the community mosque is regarded primarily as a place for congregational worship, for hosting of dakwah and Islamic learning activities and to hold congregational affairs that open the opportunity to bring together the Islamic community. Analysis of the spatial zoning and arrangements of the two community mosques shows similar concerns in spatial planning, where the focuses are on hierarchy of space, placement of mihrab and minbar, flexibility to cater for change in volume of Jemaah, gender segregation and integration issues, flow of worship processes, and space hierarchy. Users concerns mainly focus on accessibility, audibility, privacy, cleanliness and hygiene, safety and thermal comfort. Space provisions that users feel that are currently under provided are spaces and facilities to support social gathering activities, seminars and funeral preparations.